Establishment and Evaluation of a Moderate-to-Severe Knee Osteoarthritis Model in Rats Induced by Surgery - SUN Xiaorong; SU Dan; GUI Wenjuan; CHEN Yue (Shiyan dongwu yu bijiao yixue)
ObjectiveTo establish a rat model of moderate-to-severe knee osteoarthritis, laying the foundation for studying the pathogenesis of moderate-to-severe knee osteoarthritis and its prevention and treatment methods.MethodsThirty male SD rats were randomly divided into three groups: a sham surgery group, an 8-week model group, and a 20-week model group, with 10 rats in each group. Rats in the 8-week and 20-week model groups underwent surgery to cut the anterior and posterior cruciate ligaments and medial collateral ligament of the right knee joint, and remove the medial and lateral menisci. After surgery, the rats were allowed to move freely. The rats in the sham surgery group had only skin incisions to expose the joint without any surgical treatment. At 8 and 20 weeks post-surgery, Micro-CT scans were performed to analyze the femoral osteoporosis in the rats. After euthanizing the rats, gross observations of the knee joints were made, and the cartilage of the joint surface was scored using the Pelletier scoring system. The knee joints were collected for hematoxylin and eosin (HE) staining and safranin O-fast green staining to observe changes in cartilage morphology. The modified Mankin's scoring system was used to assess the tissue pathology of the joint surface. Immunohistochemical staining was used to detect the expression of type II collagen and matrix metalloproteinase 13 (MMP13), reflecting the anabolic and catabolic metabolism of the knee joint cartilage.ResultsThe knee joint cartilage in the 8-week and 20-week model groups was severely damaged, with Pelletier and modified Mankin's scores significantly higher than those in the sham surgery group (both P<0.01). The Pelletier and modified Mankin's scores in the 20-week model group were significantly higher than those in the 8-week model group (P<0.01). Micro-CT observations revealed irregular joint surfaces, osteophyte formation, and signs of osteoporosis in both the 8-week and 20-week model groups, with the 20-week model group showing more loose bodies around the knee joints. Immunohistochemical staining showed increased expression of MMP13 and decreased expression of type II collagen in the knee joint tissues of the model groups, indicating that the balance of anabolic and catabolic metabolism in the joint cartilage was disrupted. MMP13 increased while type II collagen decreased.ConclusionThe surgical method of cutting the anterior and posterior cruciate ligaments and medial collateral ligament and removing the medial and lateral menisci successfully creates a moderate-to-severe knee osteoarthritis model in rats. Imaging examinations reveal osteophytes, osteoporosis, and loose bodies in the knee joints, while pathological observations show a reduction or even disappearance of joint cartilage, with a disruption in the balance of cartilage anabolic and catabolic metabolism.